2016
DOI: 10.5966/sctm.2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

The Cleavage Effect of Mesenchymal Stem Cell and Its Derived Matrix Metalloproteinase-2 on Extracellular α-Synuclein Aggregates in Parkinsonian Models

Abstract: Ample evidence has suggested that extracellular α‐synuclein aggregates would play key roles in the pathogenesis and progression of Parkinsonian disorders (PDs). In the present study, we investigated whether mesenchymal stem cells (MSCs) and their derived soluble factors could exert neuroprotective effects via proteolysis of extracellular α‐synuclein. When preformed α‐synuclein aggregates were incubated with MSC‐conditioned medium, α‐synuclein aggregates were disassembled, and insoluble and oligomeric forms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 64 publications
2
38
0
Order By: Relevance
“…Several extracellular proteases are known to cleave αSyn, e.g. plasmin 32 , neurosin 33,34 and several metalloproteinases [35][36][37][38] . Although we were not able to identify the active protease (s) in our experimental system, a comparison between our MS data and previously published cleavage sites of αSyn suggests that plasmin and matrix metalloproteases 3 and 9 could be suitable candidates 32,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Several extracellular proteases are known to cleave αSyn, e.g. plasmin 32 , neurosin 33,34 and several metalloproteinases [35][36][37][38] . Although we were not able to identify the active protease (s) in our experimental system, a comparison between our MS data and previously published cleavage sites of αSyn suggests that plasmin and matrix metalloproteases 3 and 9 could be suitable candidates 32,36 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that MSCs can migrate to injury sites and secrete various neurotrophic factors that exert neuroprotective effects [15,24], via anti-apoptotic [25], supportive (i.e., stimulation of mitosis, proliferation, and differentiation) [26], and angiogenic effects [25]. In our previous experimental studies, we have demonstrated the therapeutic potential of MSCs in animal models of parkinsonian disorders through antiin ammatory action [27], autophagy modulation [28], stabilization of axonal transport [18], control of microglia M2 polarization [29], proteolysis of α-synuclein aggregates [17], and inhibition of α-synuclein transmission [16], which might modulate α-synuclein-related microenvironments. Furthermore, in two previous clinical trials [12,13], we demonstrated the safety and clinical e cacy of intra-arterial and intravenous administration of autologous BM-MSCs in patients with MSA-C.…”
Section: Discussionmentioning
confidence: 99%
“…Only the administration of autologous mesenchymal stem cells (MSCs) via the intra-arterial/intravenous [12,13] or intrathecal routes [14] have shown any effect. Indeed, MSCs secrete various cytokines and growth factors that exert neuroprotective effects [15] and directly modulate α-synuclein-related neurodegeneration [16][17][18][19]. As such, MSCs may be the most suitable candidate for MSA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the proteomic analysis of the secretome, we found that BM-MSCs secreted not only important neurotrophic factors, such as vascular endothelial growth factor (VEGF), BDNF, interleukin-6 (IL-6) and GDNF, but also other potential neuroregulatory molecules, namely cystatin C (Cys C), glia-derived nexin, galectin-1, and PEDF [38]. Recently, it was also demonstrated the ability of MSCs secretome to degrade extracellular α-synuclein both in vitro and in vivo, an effect partially mediated by matrix metalloproteinase-2 (MMP-2) [39].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%